Archaeology and Hauntology: An Ongoing, Stalled Conversation - Colby Dickinson (Religions, 2023)
It is certainly possible that we might learn to better acknowledge the spirits of our ancestors who came before us, as well as to recognize them in such ways that we also learn to embrace the ‘woven density’ of our own lives, our histories and our communities. By doing so, we might begin to discover that the spirits we had thought were removed from our modern, secularized world never fully left us, just as the irrationality of our humanity cannot be fully tamed via a reductive, rational and scientific outlook on life. There are, as Bruno Latour had frequently argued, many modes of human existence that interact in complex networks of relations. To fall back on any one particular mode as if it could dominate over others would only grant us a mistaken impression of our own humanity, even though this is what has been practiced for centuries in order to legitimate a particular, sovereign configuration of power. It is to the credit of archaeologists and hauntologists alike that we are more able than ever to take account of the complexity of ourselves in ways that we had previously ignored or repressed.